The Psychological and Financial Impact of Long-distance Travel for Liver Transplantation. Issue 6 (June 2020) - Peretz, David; Grubert Van Iderstine, Micah; Bernstein, Matthew; Minuk, Gerald Y.
Abstract : Background: Patients who travel long distances to undergo liver transplantation have limited opportunities to develop confidence in their new healthcare providers and experience fewer support visits from family and friends at the transplant site. The objectives of this study were to document the psychological and financial impact of having to travel long distances for liver transplantation in adult liver disease patients. Methods: This was a single-center, prospective study that used a 7-question survey, including Likert scales, patient recall, and administrative databases. Results: Ninety-six adult outpatient liver transplant recipients (59% males; mean age, 43.1 ± 2.1 y) participated in the survey. Approximately 70% (more so among males and higher educated patients) felt that they had sufficient time to develop confidence in their new healthcare providers and 87% felt that confidence in their local healthcare providers had not been diminished by undergoing the procedure elsewhere. Forty-four percent of patients felt that their overall liver transplant experience had been compromised by more limited opportunities for support visits, a perception that was twice as common in females. Median out-of-pocket expenses were under $5000, and inflation corrected costs to third-party payers have been stable for the past 20 y. Conclusions: The principal psychological impact of travelling long distances for liver transplantation relates to the consequences of fewer support visits. Confidence in the new and local healthcare teams is not compromised by such travel in most patients. Out-of-pocket expenses are under $5000, and transplant costs to third-party payers have remained stable over the past 20 y.